Sistem Pendukung Keputusan Kontribusi Optimal pada Produk Pompa Air dan Mesin Mollen dengan Pendekatan Program Linier Metode Simplex - Dewi Handayani Untari Ningsih; Sunardi .; Arief Jananto (Universitas Stikubank, 2003)
Decision Support System couple the intellectual resource of individuals with the capabilities of the computer to improve the quality of decision. It's a computer based support system for management decision makers who deal with semi-structured problem. An integrated decision support system for use in an machine mollen product has been developed. It incorporates a linear Programming model that represents the contribution optimal and optimizes the production water pump and mollen machine. An optimization model is performed using a management scient model called linear programming approach in older to determine media selection. To use this model, the DSS needs ti interface with another software. Mathematical Programming is a technique used in mathematical models, particularly optimization models, to assist in decision making. The Simplex Method is